The Equitable Income Distribution in Islam Through Transmigration: Phenomenological Study of Merbau Village, Riau - Retnowati, May Shinta; Sukma, Arti Mutiara; Averro, Muhammad Faruq (LP2M UIN KH.Achmad Siddiq Jember, 2024)
Population movement between islands in Indonesia is known as transmigration. Since the colonial era, this program has existed, even pioneered by the Dutch government for the first time with the aim of obtaining more colonial benefits. Currently, the transmigration program is growing rapidly in the eyes of the Indonesian government. Even the people themselves also volunteered to carry out transmigration in order to get better livelihoods in new areas. Not infrequently among these communities who experience difficulties during the beginning after the move. So that this transmigration community does not find work causes unemployment everywhere and makes the Indonesian economy decline. The purpose of this study is to analyze how to control unemployment in Merbau village through fair income distribution according to the perspective of the Islamic economy. This research is descriptive qualitative and collects information from interviews with local residents and describes this control from the perspective of Islamic economics. The result of this study is to describe the model of unemployment risk control in Merbau Village from a sharia economic perspective, namely the wage system. The wage / ujrah system is imposed in accordance with the agreement of both parties and gives satisfactory results to each other. And also maintain the old culture of the community to live in harmony between residents even though they are different.